The effect of isotretinoin on depression and anxiety in patients with acne vulgaris: A prospective study (Annals of Medical Research, 2021)
Aim: The aim of this study was to evaluate the effect of isotretinoin on depression and anxiety.Material and Methods: Beck depression and Beck anxiety scales were performed by the clinician before the initiation of isotretinoin therapy. At follow-up, 0.5 mg/kg/day isotretinoin was administered to the patients. In the third month of the treatment, 39 patients were reevaluated with the same scales.Results: There was no statistically significant difference in pre-treatment (11.38±12.48) vs. post-treatment (10.48±9.77) change in Beck anxiety scale points. Similarly, although there was a decrease in the Beck depression scale scores in the pre-treatment (10.05±9.02) and post-treatment (8.74±9.45) scores, no significant difference was found. Although the decrease in scores was not statistically significant, the decrease in both depression and anxiety scores after treatment showed a statistically significant correlation in itself (p0.01).Conclusions: As a result, in this study, we determined that isotretinoin treatment does not reveal any psychiatric symptoms and the current anxiety decreases depressive symptoms. For more clear findings, screening of the side effect profile with extensive and multicentre studies will contribute to the literature.Keywords: Isotretinoin; depression; anxiety; acne vulgaris.